Consumers’ buying interest to purchase pixy beauty products in Ambon City: The influence of beauty vlogger endorse and brand personality - Nurul Islamiah Raharusun; Aisah Asnawi; Etvin Rizal Tamher (President University, 2021)
The development of the internet has given rise to various platforms in promoting products variety. One of the platforms that are currently being a reference for internet users is vlogs. The influence of a vlogger can be influentially positive for increasing sales of a product.This research examines and analyzes the influence of the beauty vlogger endorsements and brand personality variables on the buying interest of Pixy beauty products in Ambon city. It takes samples from women in Ambon city interested in buying Pixy beauty products since they are influenced by endorse reviews from beauty vloggers and are strengthened by the brand personality of Pixy products.This research uses a questionnaire method as a data collection tool for as many as 108 respondents with purposive sampling. The method used in this research is quantitative analysis with multiple linear regression using the SPSS (Statistical Package for Social Science) data analysis program version 25.The multiple regression analysis test results show that the beauty vlogger endorse variable has a positive and significant influence on buying interest with a regression result of 0.230. The brand personality variable has a positive and significant impact on purchase interest with a regression result of 0.486. It indicates that brand personality is more assertive in shaping consumer buying interest than beauty vloggers. Therefore, companies must keep trying to form and strengthen brand personality to create a positive impression in the minds of consumers.